2021
DOI: 10.1016/j.biomaterials.2021.121159
|View full text |Cite
|
Sign up to set email alerts
|

Generation of potent cellular and humoral immunity against SARS-CoV-2 antigens via conjugation to a polymeric glyco-adjuvant

Abstract: The SARS-CoV-2 virus has caused an unprecedented global crisis, and curtailing its spread requires an effective vaccine which elicits a diverse and robust immune response. We have previously shown that vaccines made of a polymeric glyco-adjuvant conjugated to an antigen were effective in triggering such a response in other disease models and hypothesized that the technology could be adapted to create an effective vaccine against SARS-CoV-2. The core of the vaccine platform is the copolymer p(Man-TLR7), compose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…The purine-rich RNA is a natural ligand for TLR7, which induces the innate immune response to the invading pathogen (22)(23)(24)(25). Due to the important role of TLR7 in activating the immune system, many studies focused on the conjugation of TLR7 agonists to antigens for enhancing immune responses (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…The purine-rich RNA is a natural ligand for TLR7, which induces the innate immune response to the invading pathogen (22)(23)(24)(25). Due to the important role of TLR7 in activating the immune system, many studies focused on the conjugation of TLR7 agonists to antigens for enhancing immune responses (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has forced material engineers to develop and search for alternative materials capable of inactivating SARS-CoV-2 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In this regard, sodium alginate (SA) has shown antiviral activity against several types of viruses [ 9 ] and has been seen to possess excellent chemical, physical, and biological properties that render this biopolymer very useful for an immense range of industrial applications [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jeffrey and colleagues developed another S protein-based vaccine platform called Man-TLR7. They found that this polymeric glycol-adjuvant improved the immunogenicity of the S protein by inducing a powerful neutralizing humoral immune response and highquality cellular immune responses [56]. Pamela's team invented an intranasal vaccine candidate, which formulated S protein with a nanoemulsion (NE) that activated NLRP3 and TLRs with the RNA agonist RIG-I (IVT DI).…”
Section: Other Adjuvantsmentioning
confidence: 99%